2021
DOI: 10.21203/rs.3.rs-753298/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remote Medical Scent Detection of Cancer and Infectious Diseases With Dogs and Rats: a Systematic Review

Abstract: Background: Remote medical scent detection of cancer and infectious diseases with dogs and rats has been an increasing field of research these last 20 years. If validated, the possibility of implementing such a technique in the clinic raises many hopes. This systematic review was performed to determine the evidence and performance of such methods and assess their potential relevance in the clinic.Methods: Pubmed and Web of Science databases were independently searched based on PRISMA standards. We included stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…In this way, specific volatile biochemical fingerprints may be detected and function as biomarkers for corresponding diseases and their clinical course, provided that appropriate sensory means are available ( 18 , 19 ). The detective olfactory potential of dogs and other animals has been researched in the medical field concerning various infectious viral, bacterial, and parasitic as well as non-infectious diseases and disorders like epilepsy, diabetes, and cancer ( 5 , 11 , 20 , 21 ). Horvath et al demonstrated that dogs can differentiate between normal and neoplastic tissue as well as non-neoplastic disease processes such as inflammation, necrosis or emergence of metabolic products ( 22 ).…”
Section: Disease- or Metabolism-derived Volatile Organic Compoundsmentioning
confidence: 99%
“…In this way, specific volatile biochemical fingerprints may be detected and function as biomarkers for corresponding diseases and their clinical course, provided that appropriate sensory means are available ( 18 , 19 ). The detective olfactory potential of dogs and other animals has been researched in the medical field concerning various infectious viral, bacterial, and parasitic as well as non-infectious diseases and disorders like epilepsy, diabetes, and cancer ( 5 , 11 , 20 , 21 ). Horvath et al demonstrated that dogs can differentiate between normal and neoplastic tissue as well as non-neoplastic disease processes such as inflammation, necrosis or emergence of metabolic products ( 22 ).…”
Section: Disease- or Metabolism-derived Volatile Organic Compoundsmentioning
confidence: 99%
“…In our knowledge, there are no established applications using detection dogs in this context. The limitations of this approach are well outlined in the review by Bauer et al (Bauër et al, 2022b). These drawbacks notably include the associated high costs of employing qualified personnel for such applications, and the challenge of consistently sourcing samples for dogs' trainings, to maintain their performances over time (Bauër et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…One crucial factor to consider is that dogs are living beings and exhibit variability in their responses. Interpretation of canine olfaction analyzes must account for the variability among individual animals and among dog's breeds (Bauër et al, 2022b).…”
Section: Use Of the Dog As An Analytical Toolmentioning
confidence: 99%
See 2 more Smart Citations